Pola Hubungan Salinitas, Oksigen Terlarut dan pH Terhadap Bakteri Vibrio sp. pada Lokasi Budidaya Udang (Litopenaeus vannamei) di Kabupaten Kolaka - Arman Pariakan; Rahim Rahim; Indrayani Indrayani (Samakia : Jurnal Ilmu Perikanan, 2023)
The sustainability of vannamei shrimp (L. vannamei) aquaculture activities is very dependent on the health of the vannamei shrimp being reared, the health of the vannamei shrimp is greatly influenced by biotic (pathogenic bacteria) and abiotic (environmental stress) factors which together affect their survival. This study aims to analyze the relationship and distribution of salinity, dissolved oxygen, and pH variables for the distribution of Vibrio sp. The results show that the salinity has a strong effect on the presence of Vibrio sp. in the shrimp pond area with a value of 0.008495, while pH and dissolved oxygen did not have a strong influence on the presence of Vibrio sp. bacteria with values ​​​​of 0.470479 and 0.663797 respectively. Therefore, it was concluded that it is important to control the salinity value so that it is not too high or too low with a value in the range of 18 – 20 ppt. Then even though pH and dissolved oxygen do not affect the presence of bacteria, these two parameters greatly affect the vannamei shrimp immune system which can make it easier for Vibrio sp. bacteria to develop and infect.